2014
DOI: 10.2527/jas.2014-7932
|View full text |Cite
|
Sign up to set email alerts
|

Beta agonists in livestock feed: Status, health concerns, and international trade

Abstract: Since the U.S. Food and Drug Administration approved ractopamine hydrochloride and zilpaterol hydrochloride in animal feeds, usage of those compounds has been a topic of worldwide debate. Ractopamine and zilpaterol are β-adrenergic agonists used as veterinary drugs to increase weight gain in certain animals raised for food. The Joint FAO/WHO Expert Committee on Food Additives (JECFA) established maximum residue limits for ractopamine, which were adopted by the Codex Alimentarius Commission (Codex). No maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 12 publications
0
39
0
Order By: Relevance
“…Several studies since the early 1980s have demonstrated that beta 2 ‐agonists elicit muscle hypertrophy, increase muscle strength, and reduce fat mass in a variety of mammalian species . Due to these actions, beta 2 ‐agonists have been adopted in the feeding of livestock for repartitioning purposes to increase efficiencies of meat production . In addition, beta 2 ‐agonists are commonly applied in hypertrophic model systems to examine cellular signalling pathways of importance for muscle growth with applicability for drug development .…”
Section: Anabolic and Lipolytic Effects Of Beta2‐agonistsmentioning
confidence: 99%
“…Several studies since the early 1980s have demonstrated that beta 2 ‐agonists elicit muscle hypertrophy, increase muscle strength, and reduce fat mass in a variety of mammalian species . Due to these actions, beta 2 ‐agonists have been adopted in the feeding of livestock for repartitioning purposes to increase efficiencies of meat production . In addition, beta 2 ‐agonists are commonly applied in hypertrophic model systems to examine cellular signalling pathways of importance for muscle growth with applicability for drug development .…”
Section: Anabolic and Lipolytic Effects Of Beta2‐agonistsmentioning
confidence: 99%
“…Nevertheless, the assumption that zilpaterol affects growth and/or body composition, and may enhance athletic performance or competitive advantage, has caused a multitude of competition organizations to ban zilpaterol completely in animals and humans (ARCI 2018;HLSR 2018;WADA 2018). Additionally, zilpaterol is banned for use in beef and other food-animal species by most countries (Centner et al 2014) and, consequently, zilpaterol in edible tissues of any species is considered violative by numerous international regulatory agencies.…”
Section: Introductionmentioning
confidence: 99%
“…Two b-adrenergic agonists are approved for use in cattle fed in confinement for slaughter in the United States, namely, zilpaterol hydrochloride and ractopamine hydrochloride, with the purpose of increasing the rate of gain, improving feed efficiency and increasing carcass leanness (Delmore et al 2010;Brown et al 2014;Martin et al 2014). Maximum residue limits for ractopamine determined by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) were adopted by the Codex Alimentarius Commission (Codex), although no such limits have been determined for zilpaterol (Centner et al 2014). Many countries disagree with the Codex standards and maintain a policy of restricting or banning meat products containing b-agonists (Centner et al 2014), whereas other countries have fewer concerns.…”
Section: B-adrenoceptor Agonistsmentioning
confidence: 99%
“…Maximum residue limits for ractopamine determined by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) were adopted by the Codex Alimentarius Commission (Codex), although no such limits have been determined for zilpaterol (Centner et al 2014). Many countries disagree with the Codex standards and maintain a policy of restricting or banning meat products containing b-agonists (Centner et al 2014), whereas other countries have fewer concerns. Methods are being developed to manage the safety of imported meat products from countries where zilpaterol use is still permitted, to prevent b-agonist poisoning due to secondary contamination (Sung et al 2015).…”
Section: B-adrenoceptor Agonistsmentioning
confidence: 99%